Peranan UMKM Di Desa Kajang Untuk Meningkatkan Kesejahteraan Masyarakat Dalam Tinjauan Maqāşid Syarī’ah - Cholifah Karunia Karunia; Unun Roudlotul Janah (Niqosiya: Journal of Economics and Business Research, 2023)
Introduction: UMKM is the most strategic sector of the national economy and concerns the lives of many people so that they become the backbone of the national economy. Such is the case with UMKM in Kajang Village, Sawahan District, Madiun Regency, which makes UMKM an effort to improve welfare. Research Methods: The research method used is a qualitative descriptive research method which is a problem-solving procedure by describing circumstances based on facts that appear as they are. Results: The existence of UMKM can provide benefits to the community supported by an increase in the number of UMKM in Kajang Village and can improve the quality of human resources which are expected to have many new innovations able to meet the four benchmarks of community welfare and also the three levels of sharia maqasid. The obstacles faced come from internal factors and external factors. Conclusion: UMKM in Kajang Village has a very important role in the community which is able to open new job opportunities. The people of Kajang Village have met all four indicators, namely income, residential housing, education, and health. In the analysis of maqāṣid syarī'ah, the people of Kajang Village have fulfilled three levels, namely dharuiriyyah, hajiyyah, and tahsiniyyah.